Android-based GymAp application to improve handstand skills in gymnastics learning among high school students - Handayani, Sri Gusti; Myori, Dwiprima Elvvany; Komaini, Anton (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to develop a valid, practical, and effective gymnastics instruction media to improve students' handstand skills in gymnastics education. The development process followed the Plomp model. The study involved 60 students from the Faculty of Sports Sciences of Universitas Negeri Padang, Indonesia. Data were collected through tests, interviews, questionnaires, and observations and assessed quantitatively through the use of a t-test. The findings indicated that the Android-based gymnastics educational media demonstrated very high validity across material, media, and language assessments, as well as in handstand skill evaluation tools. The media was also rated as very practical and very effective. The average initial handstand skill scores across three schools were 83.65, 84.65, and 73.45, with average improvement scores of 0.61, 0.65, and 0.64, respectively. These results indicate that the android-based gymnastics learning media is valid, practical, and effective in enhancing students’ handstand skills. It is anticipated that this media will serve as an alternative resource for improving the quality of gymnastics education and other related academic disciplines.